Adaptive Radiation from a Chromosomal Perspective: Evidence of Chromosome Set Stability in Cichlid Fishes (Cichlidae: Teleostei) from the Barombi Mbo Lake, Cameroon - Majtánová, Zuzana; Indermaur, Adrian; Nyom, Arnold Roger Bitja; Ráb, Petr; Musilová, Zuzana (International journal of molecular sciences, 2019)
Cichlid fishes are the subject of scientific interest because of their rapid adaptive radiation, resulting in extensive ecological and taxonomic diversity. In this study, we examined 11 morphologically distinct cichlid species endemic to Barombi Mbo, the largest crater lake in western Cameroon, namely Konia eisentrauti, Konia dikume, Myaka myaka, Pungu maclareni, Sarotherodon steinbachi, Sarotherodon lohbergeri, Sarotherodon linnellii, Sarotherodon caroli, Stomatepia mariae, Stomatepia pindu, and Stomatepia mongo. These species supposedly evolved via sympatric ecological speciation from a common ancestor, which colonized the lake no earlier than one million years ago. Here we present the first comparative cytogenetic analysis of cichlid species from Barombi Mbo Lake using both conventional (Giemsa staining, C-banding, and CMA3/DAPI staining) and molecular (fluorescence in situ hybridization with telomeric, 5S, and 28S rDNA probes) methods. We observed stability on both macro and micro-chromosomal levels. The diploid chromosome number was 2n = 44, and the karyotype was invariably composed of three pairs of meta/submetacentric and 19 pairs of subtelo/acrocentric chromosomes in all analysed species, with the same numbers of rDNA clusters and distribution of heterochromatin. The results suggest the evolutionary stability of chromosomal set; therefore, the large-scale chromosomal rearrangements seem to be unlikely associated with the sympatric speciation in Barombi Mbo.
Keywords: Animals; biologická evoluce; Chromosomal Instability; cichlidy; Chromosome Banding; karyotypizace; mapování chromozomů; jezera; Chromosome Mapping; Karyotyping; telomery; Telomere; Kamerun; Cameroon; karyotyp; Cichlids; Karyotype; biologická adaptace; chromozomální nestabilita; hybridizace in situ fluorescenční; Lakes; zvířata; Biological Evolution; In Situ Hybridization, Fluorescence; Adaptation, Biological; pruhování chromozomů